PENGARUH BUDAYA ORGANISASI, KOMPENSASI DAN IKLIM ORGANISASI TERHADAP KINERJA PEGAWAI DI KANTOR DINAS KEPENDUDUKAN DAN CATATAN SIPIL KOTA MEDAN - Adjhie Mawisguna; Fajar Rezeki Ananda Lubis; Michelle Paulina Munthe; Thezar Fiqih Hidayat Hasibuan (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This research aims to investigate the impact of organizational culture, compensation, and organizational climate on the performance of Civil Servants at the Office of Population and Civil Registration in Medan City. The respondents in this study are the Civil Servants working in this office. The analysis method applied utilizes the SMART PLS technique, which helps in assessing the validity and reliability of the variables and identifying whether the independent variables contribute positively or negatively to the performance of the Civil Servants. Through this approach, it is expected to gain a deeper understanding of the various factors influencing the performance of Civil Servants at the Office of Population and Civil Registration in Medan City.